Corrosion of Carbon Free and Bonded Refractories for Application in Steel Ingot Casting. Issue 8 (1st April 2016) - Fruhstorfer, Jens; Dudczig, Steffen; Gehre, Patrick; Schmidt, Gert; Brachhold, Nora; Schöttler, Leandro; Aneziris, Christos G.
Abstract : This phenomenological study investigates the corrosion of refractories by a highly corrosive steel (1.6587, 18CrNiMo7‐6) with a high aluminum content and casting temperature of 1580 °C. The applied refractory castables with matrices based on alumina, mullite, and zirconia/titania doped alumina (AZT) are carbon free or low carbon (4 wt%) containing with and without nanoscaled additives. The corrosion is analyzed mainly by microscopy after the corrosion tests. The carbon containing samples are negligibly corroded due to inhibited wetting. The nanoadditives in the carbon containing samples show no influence on the corrosion. The carbon free AZT is attacked most strongly with a corrosion layer of about 14 mm. In the alumina (corrosion layer about 6 mm) and AZT sample, compositions corresponding to manganese aluminates form with manganese from the steel. When also silicon diffuses into the refractory, compositions referring to manganese aluminosilicates form. In the mullite matrix crucible (corrosion layer about 1 mm) compositions corresponding to manganese aluminosilicates form directly with manganese from the steel resulting in a highly viscous melt at the interface which retard the further attack. For a future final evaluation, however, also the steel quality has to be taken into account as will be studied by an Aspex‐SEM. Abstract : Alumina and alumina–zirconia–titania matrix materials are corroded stronger than mullite matrix materials . During corrosion of the mullite refractory, a high‐viscous melt forms at the steel‐refractory interface which retards the further attack. The carbon containing samples are negligibly corroded. Surprisingly, the nanoscaled additives in the carbon containing samples show no influence on the corrosion.